A saúde na prestação dos serviços de limpeza urbana e gestão de resíduos sólidos diante dos elementos do direito à cidade: análise da efetividade nos municípios do Salvador, São Paulo e Bogotá, na Colômbia - Guimarães, Angélica Maria Santos (2017)
The core of the present study is urban clean-up and solid waste management in large Brazilian cities of Salvador and Bogotá in Colombia as a constituent element of the right to the city. Initially, the analysis differentiates the Urban Law from the Right to the City. In the sequence, it focuses on the urban cleaning in the context of the Social State and its effectiveness, analyzing the normative treatment of the topic in the context of the Brazilian legal system, including individual and concrete standards produced by the Courts of Auditors in implementing indirect execution of these services. The main objective is to defend the need of redefine of the concepts of effectiveness of such services through the adoption of a control based on principles, requirements, assumptions, indicators of public health, quality of life and environmental sustainability, emphasizing the elements and functions of the city, prescribed in the Federal Constitution, the National Solid Waste Policy and the City Statute. It is evaluated the role of the Welfare State in urban cleaning and solid waste management, understood as socio-environmental goods of economic value, capable of transforming cities into "healthy living spaces", accomplishing of social rights, of happiness and of sustainable economic development. It defends also Urban clean-up and solid waste management are therefore advocated as a constitutive element of the Right to the City and, at the same time, guarantee instrument of leisure, education, housing, movement, employment and income in a sustainable urban environment. Urban cleaning and solid waste management must be able to assure the inhabitants of the town, physical and mental health, as well as quality of life in all its aspects